Initial evaluation of an intervention to address provider implicit bias in pediatric sickle cell disease pain care: A mixed methods pilot study - Siddika S. Mulchan; Christopher B. Theriault; Susan DiVietro; Mark D. Litt; Emily O. Wakefield; Javeed Sukhera; Paula Tanabe; Hannah R. Thomas; Melissa Santos; William T. Zempsky; Donna Boruchov; Adam T. Hirsh (Canadian Journal of Pain)
Background Health care provider (HCP) implicit bias can impact health outcomes for youth with sickle cell disease (SCD).Aims : The aim of this study was to evaluate the feasibility, acceptability, and preliminary impact of an individuation and perspective-taking (IPT) intervention to decrease implicit bias and improve pain treatment clinical decision making in pediatric SCD HCPs.Methods This mixed methods pilot randomly assigned HCPs (N = 36) to an intervention (n = 17) or control condition (n = 19). Implicit and explicit bias measures were administered pretreatment and 3 months postintervention. Differences were analyzed using repeated measures analyses of variance. HCP ratings of virtual patient vignettes depicting Black and White youth with SCD or cancer pain were used to assess differential clinical decision making based on race and diagnosis and analyzed using hierarchical linear mixed model analysis. Focus groups with intervention participants were analyzed using thematic analysis.Results No significant differences in scores on bias measures across time, condition, or the Condition × Time interaction were found (all P < 0.05). Significant differences in HCP ratings were found between types of HCPs (P < 0.001), but no effects were attributable to condition, time, virtual patient race, or diagnosis. Ten themes were extracted regarding the intervention’s format, structure, and content.Conclusions This study is the first to evaluate an IPT intervention in pediatric SCD HCPs. HCPs deemed the intervention feasible, acceptable, and impactful and suggested areas for improvement. Future research should refine the intervention to incorporate greater patient involvement and skills practice to improve health outcomes for this underserved population.